The Use of Digital Technology in Improving the Quality of Midwifery Care for High-Risk Pregnant Women at the Pulobandring Community Health Center in Asahan Regency - Sastrika Handayani Marpaung (Jurnal EduHealth, 2025)
Maternal mortality due to pregnancy complications remains a major challenge in Indonesia, requiring early detection through digital technologies such as health applications and wearable devices. Objective: This study aims to examine the impact of digital technology utilization on the quality of midwifery care for high-risk pregnant women. Methods: This study used a quasi-experimental quantitative design with a pretest–posttest with control group design at the Pulobandring Community Health Center. A sample of 60 high-risk pregnant women was selected using purposive sampling and divided into an intervention group (digital-based care) and a control group (conventional care). Data was analyzed using paired and independent t-tests. Results: The intervention group showed a significant increase in ANC visit compliance (90%, p=0.002), a decrease in mean systolic blood pressure from 142.6 to 131.8 mmHg (p=0.004), and an increase in knowledge scores from 56.2 to 82.5 (p=0.000). In contrast, the control group did not show any statistically significant changes. Conclusion: The use of digital technology is effective in improving the quality of midwifery care through increased compliance, stability of health conditions, and knowledge of high-risk pregnant women.